'We Live on Estimates': Everyday Practices of Prepaid Electricity and the Urban Condition in Maputo, Mozambique. (8th January 2016) - Baptista, Idalina
Abstract: This article examines the transition to prepaid electricity happening in Maputo, Mozambique, in order to reflect on the contemporary geographies of urban energy infrastructure and urbanization in sub‐Saharan Africa and other cities of the South. The article draws on fieldwork and archival research conducted in 2013 and 2014, arguing that prepayment constitutes a productive juncture in the urban experience of electricity infrastructure in Maputo's postcolonial moment, not merely a neutral technology or a disciplining technique of government (as argued by some scholarship). The article examines the multiple rationalities implicated in the use of the electricity infrastructure via prepayment and the organization of urban life it engenders (and of which it is also a product) by focusing on the everyday practices surrounding prepaid electricity of urban dwellers in neighbourhoods where the 'modern infrastructural ideal' may never be fully realized. As a result, it contributes to an understanding of the experience of urban energy in cities where 'slum urbanism', uncertainty and provisionality are dominant aspects of the urban condition.